Vitamin D and cancer - Johnson, Candace S.; Trump, Donald L. [ (Donald Lynn)] , 1945- (New York : Springer, 2011)
Substantial data indicate the broad importance of vitamin D-based signaling in normal human physiology and the broad effects of vitamin D deficiency. Vitamin D may play a role not only in the control of bone and mineral metabolism, but also appears to be involved in immune function, cardiovascular health, thrombosis and vasculogenesis and neuromuscular function. Considerable epidemiologic data demonstrate that low vitamin D serum levels occur very commonly in normal adult populations and that vitamin D deficiency is associated with an enhanced risk of cancer death from lung, prostate, head & n
1. Vitamin D: synthesis and catabolism - considerations for cancer causation and therapy -- 2. The molecular cancer biology of the VDR -- 3. Anti-inflammatory activity of calcitriol in cancer -- 4. The epidemiology of Vitamin D and cancer risk -- 5. Vitamin D and Angiogenesis -- 6. Vitamin D: cardiovascular function and disease -- 7. Induction of differentiation in cancer cells by Vitamin D: recognition and mechanisms -- 8. Vitamin D and cancer chemoprevention -- 9. Molecular biology of Vitamin D metabolism and skin cancer -- 10. Vitamin D and prostate cancer -- 11. Vitamin D and Hematologic Malignancies -- 12. The Vitamin D signaling pathway in mammary gland and breast cancer -- 13. Vitamin D and colorectal cancer -- 14. Unique features of the enzyme kinetics for the Vitamin D system, and the implications for the cancer prevention and therapeutics -- 15. Assessment of Vitamin D status in the 21st century
Includes bibliographical references and index
Keywords: Cancer -- Treatment; Vitamin D -- Therapeutic use